TO SEE, WHILE UNABLE TO SEE: AUTOBIOGRAPHICAL PERSPECTIVES OF AN OPHTHALMOLOGIST ON THE COVID-19 PANDEMIC - C. Gouws (Acta Theologica)
The COVID-19 pandemic started spreading around the globe towards the end of 2019. In this mostly autobiographical reflection on the effects of the pandemic, vision and seeing are used as metaphors to create a narrative discerning different reactions and perspectives in a local and wider context. This narrative is augmented by excerpts and paraphrasing of literature originating during previous disruptions and times of uncertainty. The author uses examples from the Second World War, the Soviet Union in the 1950s, the civil war in the Balkans in the 1980s, and 9/11. The article consists of four sections. First, some medical and epidemiological perspectives are provided; secondly, the author’s immediate milieu is described; thirdly, perspectives of places further afield are depicted, and lastly, a reflection on the pandemic and the future. The author concludes with thoughts on Christian faith, challenging believers to hold on and persevere, despite not seeing the final outcome of this disruption.